Assessing Information Need of the Stakeholders on Good Agricultural Practices (GAP) for Grapes - Sukanya Som , R. Roy Burman , J. P. Sharma , V. Sangeetha , V. Lenin; M. A. Iquebal (Indian Journal of Extension Education, 2015)
An effort was made to assess the information need of the farmers and other related stakeholders on Good Agricultural Practices (GAP) for Grapes. The study was conducted in Nashik and Sangli districts of Maharashtra. Total 70 farmers, 35 from each of the two districts along with 19 scientists of National Research Centre (NRC) for Grapes and Krishi Vigyan Kendras (KVK), 30 line department staff and 20 exporters were selected as respondents to carry out the study. Interview schedule was prepared and administered to the farmers and related stakeholders for assessing their information need on GAP for grapes. Significant difference was found in the information level of GAP practicing and non-GAP practicing farmers. On an average 84 per cent GAP practicing farmers were found to have information on various aspects of GAP while only 45.73 per cent farmers had information on different aspects of GAP on an average. Information on certifying agencies and potential economic benefit of GAP ranked first as perceived information need of the farmers while use of chemicals and sources of credit ranked second and third, respectively. However, the other stakeholders perceived selection of variety to be the most vital information to be disseminated to farmers followed by procedure of certification and criteria of GAP. It was found that for both groups of farmers, interpersonal networks ranked first as source of information. The study implied that significant information gap existed among the farmers on GAP which needs to be bridged up by appropriate extension intervention.